Thermal Profile of Accretion Disk Around Black Hole in 4D Einstein–Gauss–Bonnet Gravity - Odilbek Kholmuminov; Bakhtiyor Narzilloev; Bobomurat Ahmedov (Universe)
In this study, we investigate the properties of a thin accretion disk around a static spherically symmetric black hole in 4D Einstein–Gauss–Bonnet gravity, with an additional coupling constant, <semantics>α</semantics>, appearing in the spacetime metric. Using the Novikov–Thorne accretion disk model, we examine the thermal properties of the disk, finding that increasing <semantics>α</semantics> reduces the energy, angular momentum, and effective potential of a test particle orbiting the black hole. We demonstrate that <semantics>α</semantics> can mimic the spin of a Kerr black hole in general relativity up to <semantics>a≃</semantics> 0.23 M for the maximum value of <semantics>α</semantics>. Our analysis of the thermal radiation flux shows that larger <semantics>α</semantics> values increase the flux and shift its maximum towards the central black hole, while far from the black hole, the solution recovers the Schwarzschild limit. The impact of <semantics>α</semantics> on the radiative efficiency of the disk is weak but can slightly alter it. Assuming black-body radiation, we observe that the disk’s temperature peaks near its inner edge and is higher for larger <semantics>α</semantics> values. Lastly, the electromagnetic spectra reveal that the disk’s luminosity is lower in Einstein–Gauss–Bonnet gravity compared to general relativity, with the peak luminosity shifting toward higher frequencies, corresponding to the soft X-ray band as <semantics>α</semantics> increases.